Conservation and Environmental Appreciation Campaign in Parelhas/RN: Building behaviors and environmental guidelines. Fiction or reality? - Pereira Filho, Evadio; Azevedo, Clebiana Santos Fernandes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The article evaluates if Conservation and Environmental Appreciation Campaign, developed in Parelhas/RN, contributes to the guidelines and environmental behaviors of the participants. A questionnaire was used to capture demographic data and levels of agreement of respondents about sixteen environmental variables. The survey instrument is an adapted version of the construct of Larson, Castleberry and Green (2010), entitled Children’s Environmental Perceptions Scale (CEPS). 101 students were interviewed who are enrolled in two schools in the local segment: one public and the other private. The results demonstrated that the project under discussion has been building and solidifying behaviors and environmental values of the students. There supremacy of variables that integrate eco-consciousness, indicating that participants know how importante their role is for the act of contributing to the preservation of the environment.